Whakamomori : Māori suicide prevention : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Māori Studies at Massey University, Turitea Campus, New Zealand - Coupe, Nicole Michelle (Massey University, 2005)
Suicidal behaviour is a major public health issue globally. The incidence of suicide and attempted suicide internationally is excessive, particularly among indigenous populations. The Māori (indigenous people of New Zealand) suicide and attempted suicide rates have exceeded the non-Māori rates in New Zealand. In an attempt to address the high incidence of Māori suicidal behaviour an epidemiological case control study was initiated. Method: 250 consecutive cases of Māori who attempted suicide who were admitted to one of the three Auckland public hospitals were compared to 250 random, Māori community-based controls (found through door knocking). Participants were compared on a variety of measures including the General Health Questionnaire-28 (GHQ-28), Hospital Anxiety and Depression Scale (HADS), CAGE Alcohol Screening Test; Composite International Diagnostic Interview (CIDI-suicidality), Beck's Scale of Suicide Intent (SIS); and cultural identity validated questionnaires. Results: Response rates were high for both cases (85.6%) and controls (81.2%). The multivariate analysis revealed that poor general health status was the key risk factor associated with attempted suicide among Māori. Once the health indicator is taken out of the analysis, cultural identity, marijuana utilisation and interpersonal abuse are the next major risk factors in attempted suicide among Māori. Conclusion: Suffering from poor general health can increase attempted suicide among Māori. Having a notional identity and not being connected to Māoritanga (those things Māori; Māori culture) is associated with the risk of suicidal behaviour.
Keywords: Suicidal behaviour; Suicide; Fields of Research::370000 Studies in Human Society::379900 Other Studies In Human Society::379902 Indigenous studies